A case of mixed dementia with atypical presentation in a veteran - Sujan Poudel; Tejas Patel; Jhoanne Paras; Berdith Lebrun; Gerardo Ferrer; Prerana Upadhyaya; Nisha Panta; Syed Rizvi; Sultan Ahmed (Journal of Preventive and Complementary Medicine)
Background: Dementia is an increasingly pressing concern both in the United States and globally, driven by an aging population and improved life expectancy. The condition encompasses a variety of etiologies and presents a spectrum of symptoms, complicating the diagnostic process. This complexity is further heightened in the veteran population. In this report, we present a case study of a veteran experiencing atypical dementia symptoms.Case Presentation: Our subject is a veteran, a demographic that necessitates special attention due to unique health challenges. This individual exhibit cognitive decline characterized by atypical symptoms, including fugue states, recurrent episodes of flight, and significant amnesia. This case study explores the concurrent pathologies to better delineate the etiology of dementia, highlighting an essential aspect of geriatric healthcare.Discussion: This case highlights the complexities of diagnosing and managing dementia when symptoms are atypical, particularly in patients with multiple comorbidities and intricate medical histories, such as those stemming from military service. In these instances, a patient-centered, multidisciplinary approach is not only beneficial but essential for effective dementia management, emphasizing its importance in clinical practice.